Choristomatous endocervical polyp with heterologous adipose tissue - Brij Mohan Kumar Singh; Varun Kumar Singh; Parvati Vinod Bhat (Wolters Kluwer Medknow Publications, 2021)
Endocervical polyps are a common occurrence in the postmenopausal age group and many reports have described the presence of heterologous elements in the stroma of such polyps. The presence of mature adipose tissue in the stroma has been hypothesized to be arising from the perivascular fat or metaplastic transformation of the smooth muscle cells posttrauma. A 75-year-old female presented with spotting per vagina. Colposcopic examination revealed an endocervical polyp which was excised. Microscopic examination showed an ulcerated epithelium with metaplastic changes along with sheets of mature adipose tissue with focal S100 positivity conferring a diagnosis of choristomatous endocervical polyp with heterologous adipose tissue. The primary clinical concern of a malignant cause in this age group is alleviated by the diagnosis of this rare benign entity. Only three such cases have been reported in the English literature so far, and the present case accounts for the fourth such case.